REKONSTRUKSI WEWENANG BAWASLU DALAM PENEGAKAN HUKUM PIDANA PEMILU MELALUI SENTRA GAKKUMDU - Zairudin, Ahmad (Universitas Nurul Jadid, 2023)
This study aims to determine Bawaslu's efforts in supervising and preventing violations in the 2024 election, through its duties, functions and authorities. and how the handling of election criminal acts can be resolved through the Sentra Gakkumdu. This research method uses normative juridical concepts with statutory, case and conceptual approaches. As for this study, researchers used sources of legal materials in the form of primary legal materials, secondary legal materials, and tertiary legal materials. In countries that have good and mature democracy, or developing countries that are moving towards democracy, they are still in the process of transition. In reality, elections are still marked by various frauds and violations (electoral malpractices). Elections are still filled with violations and fraud, which certainly threatens the legitimacy of elected power and undermines public trust in state institutions. Transition and consolidation are democratic processes that rely heavily on the quality of the implementation of the election administration. Presence and existence of Bawaslu based on Law no. 7 of 2017, to provide guarantees for the creation of quality and democratic elections, which are held in general, free, confidential, honest and fair (LUBER, JURDIL). The establishment of the Gakkumdu Center is an effort to strengthen Bawaslu with the authority to enforce election criminal law in the implementation of elections in Indonesia. Keywords: Strengthening, Bawaslu, Sentra Gakkumdu